PENERAPAN SISTEM APLIKASI PEMBELAJARAN PENGENALAN DASAR JARINGAN KOMPUTER TINGKAT SEKOLAH MENENGAH KEJURUAN BERBASIS MULTIMEDIA PADA SMK SWAKARYA BINJAI UNTUK MENINGKATKAN KOMPETENSI LULUSAN - Ginting, Karina Latersia br; Sari, Mega Kenanga; Pasaribu, Tio Ria; Manik, Ediman (STMIK Kaputama, 2018)
Basically the science of computer not only utilized for computing, which at this point has many created a variety of highly sophisticated technological innovation with the help of a computer. Be it in terms of multimedia support from a wide range of areas such as presentations, educational tool to entertainment Earth.The application of learning basic introduction to computer networks, created on the basis of its specific needs in the field of learning computer. Based on the author's observations about system analysis that goes about learning, then it is known that very few applications are themed learning about basic introduction to computer networking.Build applications using macromedia flash 8 learning can facilitate teachers in menyampaiakan material particularly material about a basic introduction to computer networking. The students will feel more comfortable and effective in following lessons, and the students will more readily understand and add to knowledge.